Experiences of family caregivers in the home care to people with pressure injuries - Gomes, Larissa Santana; Kochergin, Clavdia Nicolaevna; Santos, Rebeca Silva dos; Cunha, Juliana Xavier Pinheiro da (Revista de Enfermagem da UFPI, 2024)
Objectives: To analyze the experience of family caregivers in the home care for people with pressure injuries (PI). Methods: Qualitative and descriptive research carried out with family members who received support from the home care service and who were the main informal caregivers of people with PI from stage 3 onwards. A sociodemographic questionnaire and semi-structured interview were applied with the following stimulus for narration: tell me about your experience in the home care to your family member with PI? Data were analyzed according to Bardin's content analysis. Results: Four categories emerged: 1) Performance of family members in PI care; 2) Support of the home care service to the family and patients with PI; 3) Overload of family caregivers; 4) Satisfaction in repaying the care received. Conclusion: This study showed the importance of support to home care service and the difficulties experienced by family members in caring for people with PI, including financial and physical overload; lack of preparation of the caregiver to deal with PI; family conflicts; and the centralization of care responsibility, predominantly performed by women. However, many see in care the opportunity to return the love received, despite all physical and mental fatigue.